Can Machine Learning be Applied to Carbon Emissions Analysis: An Application to the CO2 Emissions Analysis Using Gaussian Process Regression - Ma, Ning; Shum, Wai Yan; Han, Tingting; Lai, Fujun (Frontiers in Energy Research, 2021)
In this paper, a nonparametric kernel prediction algorithm in machine learning is applied to predict CO2 emissions. A literature review has been conducted so that proper independent variables can be identified. Traditional parametric modelling approaches and the Gaussian Process Regression (GPR) algorithms were introduced, and their prediction performance was summarized. The reliability and efficiency of the proposed algorithms were then demonstrated through the comparison of the actual and the predicted results. The results showed that the GPR method can give the most accurate predictions on CO2 emissions.